2020
DOI: 10.1371/journal.pone.0241558
|View full text |Cite
|
Sign up to set email alerts
|

Commonly used clinical chemistry tests as mortality predictors: Results from two large cohort studies

Abstract: Background The normal ranges for clinical chemistry tests are usually defined by cut-offs given by the distribution in healthy individuals. This approach does however not indicate if individuals outside the normal range are more prone to disease. Methods We studied the associations and risk prediction of 11 plasma and serum biomarkers with all-cause mortality in two population-based cohorts: a Swedish cohort (X69) initiated in 1969, and the UK Biobank (UKB) initiated in 2006–2010, with up to 48- and 9-years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
0
3
0
2
Order By: Relevance
“…In the general population, a research conducted using data from NHANES spanning the years 1999 to 2006 revealed that participants with elevated BUN levels, compared to those in the first quartile of BUN levels, exhibited an elevated risk of dying from CVD and all-cause [ 28 ]. However, data from the UK Biobank and Health Screening Survey X69 showed that BUN levels and mortality displayed a U-shaped relationship [ 29 ]. Various similar findings have been observed in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, a research conducted using data from NHANES spanning the years 1999 to 2006 revealed that participants with elevated BUN levels, compared to those in the first quartile of BUN levels, exhibited an elevated risk of dying from CVD and all-cause [ 28 ]. However, data from the UK Biobank and Health Screening Survey X69 showed that BUN levels and mortality displayed a U-shaped relationship [ 29 ]. Various similar findings have been observed in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Leveraging data from 3,209 participants in the Framingham Heart Study, Wang et al constructed a score comprising five biomarkers (CRP, N-terminal pro-atrial natriuretic peptide, homocysteine, renin, and D-dimer) to predict all-cause mortality, with a C statistic of 0.79 for the model including age, sex, and the score [ 28 ]. In another study examining the predictivity of 11 blood biomarkers (calcium, BUN, bilirubin, ALB, hematocrit, leukocyte count, uric acid, iron, GGT, ALP, and lactate dehydrogenase) for all-cause mortality in two cohorts, adding the biomarkers into a model of traditional risk factors yielded a validated C statistic of 0.76 [ 29 ]. In our study, we excluded participants with prevalent CVD or cancer at baseline to reduce confounding by preexisting diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, several studies have revealed a U-shaped association between total bilirubin concentration and coronary heart disease [ 39 , 40 ], telomere length [ 41 ], and all-cause mortality [ 42 ]. These findings suggest bilirubin’s threshold effect on bone health.…”
Section: Discussionmentioning
confidence: 99%